2017
DOI: 10.1161/jaha.116.005253
|View full text |Cite
|
Sign up to set email alerts
|

Progression of Coronary Artery Calcium and Incident Heart Failure: The Multi‐Ethnic Study of Atherosclerosis

Abstract: BackgroundAlthough the association between coronary artery calcium (CAC) and future heart failure (HF) has been shown previously, the value of CAC progression in the prediction of HF has not been investigated. In this study, we investigated the association of CAC progression with subclinical left ventricular (LV) dysfunction and incident HF in the Multi‐Ethnic Study of Atherosclerosis.Methods and ResultsThe Multi‐Ethnic Study of Atherosclerosis is a population‐based study consisting of 6814 men and women aged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 40 publications
0
27
0
Order By: Relevance
“…Nonetheless, the results of this study suggest that subclinical atherosclerosis does not seem to be an important unifying feature in the development of subclinical LVD, so that when the two do co‐exist, the latter is less likely mediated through overall atherosclerotic burden than through shared risk factors like diabetes, renal impairment, and obesity. However, subclinical atherosclerosis may identify a cohort of those with SBHF likely to progress to Stage C heart failure 8 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, the results of this study suggest that subclinical atherosclerosis does not seem to be an important unifying feature in the development of subclinical LVD, so that when the two do co‐exist, the latter is less likely mediated through overall atherosclerotic burden than through shared risk factors like diabetes, renal impairment, and obesity. However, subclinical atherosclerosis may identify a cohort of those with SBHF likely to progress to Stage C heart failure 8 …”
Section: Discussionmentioning
confidence: 99%
“…Coronary artery calcification (CAC) provides direct evidence of coronary artery disease (CAD) in the asymptomatic stage. Although there is a strong association between CAC and incident HF, only partly mitigated after adjustment for cardiovascular risk factors, 7,8 it seems likely that this reflects the contribution of overt CAD to HF. Previous studies suggesting a link between CAC and LV dysfunction were in patients with very high burdens of CAC (≥400), 9 greater severity of LV dysfunction measured by ejection fraction, 10,11 or high baseline risk, such as those with suspected CAD or known diabetes 12,13 .…”
Section: Introductionmentioning
confidence: 99%
“…If risk-based treatment decision is uncertain after quantitative risk assessment, the 2013 guidelines recommend repeated CCS measurements. Also, CCS progression in repeated CCS measurements has recently been associated with heart failure [5].…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19] Moreover, several studies have recently shown an association between CAC and the development of heart failure. 3,4) Leening, et al reported that the extent of CAC had a clear association with the development of heart failure independent of overt coronary artery disease. 3) Bakhshi, et al showed that CAC progression assessed by serial CAC measurement was associated with incident heart failure independent of overt coronary artery disease.…”
Section: Discussionmentioning
confidence: 99%